Dauricine Attenuates Vascular Endothelial Inflammation Through Inhibiting NF-κB Pathway - Hu, Ji; Chen, Ru; An, Jie; Wang, Yilong; Liang, Minglu; Huang, Kai (Frontiers in Pharmacology, 2021)
Endothelial cells are the fundamental components of blood vessel that regulate several physiological processes including immune responses, angiogenesis, vascular tone and so on. Endothelial dysfunction contributes to the development of various diseases such as acute lung injury, and endothelial inflammation is a vital part of endothelial dysfunction. Dauricine is an extract isolated from Menispermum dauricum D.C, a traditional Chinese medical plant that can be used for pharyngitis. In this work, we found that IL-1β-induced overexpression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and E-selectin was inhibited by dauricine in primary human umbilical vein endothelial cells (HUVECs). Correspondently, adhesion of human acute monocytic leukemia cell line (THP-1) to HUVECs was decreased by dauricine. Further studies showed that dauricine inhibited the activation of NF-κB pathway in HUVECs stimulated with IL-1β. In vivo, dauricine protected mice from LPS- induced acute lung injury. In lung tissues, the activation of NF-κB pathway and the expression of its downstream genes (ICAM-1, VCAM-1 and E-selectin) were decreased by dauricine, consistent with what was found in vitro. In summary, we concluded that dauricine could alleviate endothelial inflammation by suppressing NF-κB pathway, which might serve as an effective candidate for diseases related with endothelial inflammation.